Distance Learning at Russian Universities: “Step Forward, Two Steps Back”? - O. V. Mikhailov; Ya. V. Denisova (Высшее образование в России)
This article discusses the problems associated with the possible widespread introduction of distance learning in the practice of Russian higher education. The authors discuss and analyze in detail the advantages and disadvantages of distance learning in comparison with the traditional contact learning, involving “live” communication between teacher and trainees. The paper states that the disadvantages of learning generally prevail over the advantages. It is concluded that distance learning can become predominant only in completely unique situations, in which “live” communication between people in general and teachers and students in particular, for one reason or another, should be minimized or even eliminated altogether.